2021
DOI: 10.1097/mbc.0000000000001033
|View full text |Cite
|
Sign up to set email alerts
|

Screening hemostatic defects in Saudi University students with unexplained menorrhagia: a diagnosis, which could be missed

Abstract: Bleeding disorders are a common cause of unexplained menorrhagia in adolescents. However, there is lack of information provided on Arab girls. To estimate the prevalence of coagulation factor deficiencies and platelet dysfunction among Saudi university students with unexplained menorrhagia. In this cross sectional study, 463 adolescent girls surveyed for having heavy menses for further evaluation of underlying bleeding tendencies using screening standardized questionnaire. Only 109 girls out of the total 463 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Haemostatic defects and menorrhagia are reported as factors in developing anaemia as well according to Bakr, et al 2021 [24]. Similarly, the study of Friberg, 2006 [38] reported that heavy menstrual bleeding is frequently reported in 37% of school students.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Haemostatic defects and menorrhagia are reported as factors in developing anaemia as well according to Bakr, et al 2021 [24]. Similarly, the study of Friberg, 2006 [38] reported that heavy menstrual bleeding is frequently reported in 37% of school students.…”
Section: Discussionmentioning
confidence: 91%
“…After searching and conducting a critical appraisal of the articles, 14 studies were selected for the systematic review [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. A summary of these studies is presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…PFA-100 is extensively studied in patients with (suspected) VWD. 17 18 19 21 22 23 24 26 27 28 29 30 31 32 33 34 35 36 37 43 51 52 53 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 Favaloro et al reported an overall sensitivity of 83.2% and 91.5% of the ADP and EPI cartridge respectively in a review in 2008. 79 A current analysis including all articles published before and after 2008 yielded similar test performance outcomes, as shown in Fig.…”
Section: Results Of the Point-of-care Tests In Patients With Heredita...mentioning
confidence: 99%
“…30.8% of this group were diagnosed with a hemostatic abnormality or bleeding tendency, including one case of factor V (FV) deficiency, two cases of probable platelet dysfunction, and five cases of probable vWD based on the low levels of vWF:Ag and/or vWF:RCo. 39.28% of those cases were anemic; however, only 36% [ 4 ] of them received iron supplementation [ 11 ].…”
Section: Deficiency Of Coagulation Factors In Saudi Young Adultsmentioning
confidence: 99%